Analisis Pengaruh Lingkungan Kerja dan Promosi Jabatan terhadap Prestasi Kerja Pegawai pada PT. PLN (Persero) Kantor Pusat Divisi Umum Dan Aset Properti - Adi Dwi Laksono; Aswin Naldi Sahim; Irawan R. D Budianto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The work environment and possibilities for professional growth have an impact on employee performance, which is a crucial component of organizational effectiveness. In reality, a number of workers at the General Affairs and Property Assets Division of PT PLN (Persero) Head Office believe that the promotion process and work environment have not adequately encouraged peak performance. The purpose of this study is to examine the partial and concurrent impacts of job promotion and the workplace on employee performance. The study used associative and descriptive methodologies in a quantitative manner. A census sample technique was used, and all 65 employees made up the population. Multiple linear regression and correlation analysis, both supported by SPSS software, were used to analyze the data. The results show that the work environment has a positive and strong effect on employee performance with a correlation coefficient of 0.652, while job promotion also has a positive and strong effect with a correlation coefficient of 0.655. Simultaneously, both variables significantly influence employee performance, as indicated by an R value of 0.751 and an R square of 0.564. These findings indicate that improvements in the work environment and transparent promotion practices play an important role in enhancing employee performance.